2014
DOI: 10.1073/pnas.1414290111
|View full text |Cite
|
Sign up to set email alerts
|

Ten-percent solar-to-fuel conversion with nonprecious materials

Abstract: Direct solar-to-fuels conversion can be achieved by coupling a photovoltaic device with water-splitting catalysts. We demonstrate that a solar-to-fuels efficiency (SFE) > 10% can be achieved with nonprecious, low-cost, and commercially ready materials. We present a systems design of a modular photovoltaic (PV)-electrochemical device comprising a crystalline silicon PV minimodule and lowcost hydrogen-evolution reaction and oxygen-evolution reaction catalysts, without power electronics. This approach allows for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
233
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(242 citation statements)
references
References 59 publications
0
233
0
3
Order By: Relevance
“…The ideal limiting SFE at a single absorber particle is η = 14.4% based on a light absorber with a 2.0 eV band gap 42. It is suggested that a >10% SFE is required for photocatalysis to be an economically viable resource 43, 44 …”
Section: Fundamentals Of Electrocatalytic and Photocatalytic Co2 Redumentioning
confidence: 99%
“…The ideal limiting SFE at a single absorber particle is η = 14.4% based on a light absorber with a 2.0 eV band gap 42. It is suggested that a >10% SFE is required for photocatalysis to be an economically viable resource 43, 44 …”
Section: Fundamentals Of Electrocatalytic and Photocatalytic Co2 Redumentioning
confidence: 99%
“…[50][51][52]84 More recently, materials such as CIGS and halide perovskite-based cells have been adapted into PEC cells that exceeded 10% STH efficiency. [62][63][64] Over the last decade, materials such as metal oxides, which have been developed specifically for PEC applications, have seen substantial research interest and progress. Reported STH efficiencies for devices containing metal-oxide-based active components now exceed 5%.…”
Section: Semiconductor Materialsmentioning
confidence: 99%
“…Laboratory-scale demonstrations of these systems have achieved remarkable performances. Systems based on III-V semiconductors have been developed and show efficiencies up to 18% STH using concentrated solar irradiation (19,35), whereas systems based on Si PV cells have achieved efficiencies above 10% (86)(87)(88)(89)(90)91). More recently, solution-processed perovskite-based PV components together with earth-abundant electrocatalysts have been used to drive the watersplitting reaction at high efficiency levels, up to 12.3% STH (92) (Figure 3c).…”
Section: Photovoltaics-driven Electrolysis Devicesmentioning
confidence: 99%